2022
DOI: 10.3389/fpls.2022.782159
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prediction of Fig Phenolic Acids and Flavonoids Using Mid-Infrared Spectroscopy Combined With Partial Least Square Regression

Abstract: Graphical AbstractScheme diagram showing the research methodology and analytical approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 67 publications
0
14
1
Order By: Relevance
“…Environmental factors, seasonal variations and agricultural practices (e.g. irrigation and fertilisation) are considered key pre-harvest factors influencing GSLs content in broccoli (Ilahy et al, 2020). In addition, post-harvest treatments (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental factors, seasonal variations and agricultural practices (e.g. irrigation and fertilisation) are considered key pre-harvest factors influencing GSLs content in broccoli (Ilahy et al, 2020). In addition, post-harvest treatments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, post-harvest treatments (e.g. pulsed electric field and ultrasonic treatments), packaging and storage can also irreversibly impact the content and GL profile in broccoli (Ilahy et al, 2020). Thus, it is important to monitor the levels of GSLs, both pre-and post-harvest to inform best practices that ensure broccoli GSLs are preserved or least affected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these techniques are susceptible and precise for measuring phenolic compounds (flavonoid) and can measure at nanogram and picogram levels, the applications of these techniques are often time-consuming, destructive, and generate much chemical waste. On the other hand, Joshi [ 11 ], Arslan [ 17 ], and Hssaini [ 18 ] performed phenolic compounds identification using MIR spectroscopy and a hand-held spectral analytical system and acquired a higher correlation (R 2 ) value of 0.99; still, their studies are limited and cannot provide measurements of phenolic compounds under different stress conditions (LED lights + water). The limitations of all aforementioned studies were resolved in this study by measuring the phenolic compounds of A. thaliana plants powder matrices under various stresses and acquiring a higher correlation coefficient (R 2 ) value of 0.999 and a minimum error (RMSEP) value of 0.003 mg/g.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, multiple studies were performed that have identified the phenolic compounds present in different agricultural products like yerba mate [ 14 ], Ginkgo biloba leaf [ 15 ], and Radix Salvia Miltrorrhiza extract [ 16 ] using spectroscopic techniques. Moreover, in 2020, 2021, and 2022, Arslan et al [ 17 ], Hssaini et al [ 18 ], and Joshi et al [ 11 ] predicted the phenolic compounds in puffs, figs, and moringa powder using a hand-held spectral analytical system and mid-IR spectroscopy in combination with regression analysis. However, the combined applications of FT-IR and FT-NIR spectroscopy for the non-destructive prediction of phenolic compounds in plants under different stress conditions are still limited and not yet fully explored in scientific research.…”
Section: Introductionmentioning
confidence: 99%